New horizons in light control of plant photomorphogenesis and development - Liebers, Monique; Pfannschmidt, Thomas (Frontiers in Photobiology, 2024)
Light from Sun has tremendously shaped the evolution of plants and represents one of their key triggers for proper morphogenesis and development. Energy from Sun light is converted by photosynthesis into chemical energy that ultimately drives all energy consuming processes in plants. Besides, Sun light provides information about environmental conditions or constraints and signals important parameters such as day length, time point of season, direction and intensity of illumination or spatial competition with neighbouring plants. Plants possess a sophisticated array of photoreceptors that perceive this information (photoperception) and initiate signalling pathways that control appropriate responses at developmental or physiological level. While the primary processes of photoperception are largely understood, many aspects of the subsequent signalling networks are still elusive and especially the interaction with other signalling networks is far from understood. Light represents also a highly versatile tool for scientists to study morphogenesis and development of plants by a steadily increasing number of remote sensing technologies that allow to observe plants in real time and high resolution (photodetection). Further, scientists now can even use the knowledge about photobiology and photoreceptors to construct synthetic tools that can be genetically introduced into plants to monitor internal processes (so-called biosensors). Recent technological developments in optogenetics even allow to generate tools that actively regulate gene expression or metabolism by selective illumination (photocontrol). In this perspective article we highlight progress in our understanding of light signalling and a number of selected technological improvements in photocontrol with a special focus on the areas of phytochrome signalling and plant optogenetics.